USE OF METHODOLOGICAL TOOLS IN IMPROVING THE PEDAGOGICAL SKILLS OF TEACHERS (Academia Science Repository, 2023)
In this article, the use of pedagogical software tools in the educational process of training educators of future preschool educational organizations provides a number of new opportunities and advantages for both the teacher and the student compared to the traditional teaching method.